PENYIDIKAN TINDAK PIDANA KESUSILAAN MELALUI MEDIA SOSIAL BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2011 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK OLEH DIREKTORAT RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH KEPULAUAN RIAU - Aulia Rahmi; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The development of the world of information technology, the more people who use it as one part of the necessities of life. The need for information for example by information technology we were able to meet the needs of the information easily and quickly in a way to open the news website cia the internet network. In Indonesia itself a computer is often the case because the security system inadequate and the laws regarding information technology in Indonesia that aren’t as strong. The rise of cases of dissemination of immoral photos through social media is one of the computer crimes that occur at this time. The distribution of such immoral photos is not only done through social media but also distributed directly to friends and family of the victim and then write words that are inappropriate to say. This is where the role of law enforcement officers, especially the police in conducting investigations and investigations so that the case does not happen again. But the facts are found, the investigator can only conduct an investigation if the perpetrator has a clear identity so that no detention of perpetrators.This study uses a kind of sociological juridical research that sees the correlation between law and society. This research was conducted at Sub Directorate II of Directorate of Special Criminal Investigation of Riau Islands Regional Police, while population and sample are all related parties in problem to be studied. Sources of data used, primary data, secondary data, and tertiary data, data collection techniques in this study by interviews, and literature review.From the research there are three main points that can be concluded, the first process of investigation of criminal cases of morality through social media is still not running properly that has been regulated in legislation, where perpetrators who allegedly committed crimes are not held detention. Secondly, the need for experts with more than one expert where the unavailability of experts who master the technology and information, but to ask for expert information must wait from the Police Headquarters of the Republic of Indonesia. Third, the lack of facilities and infrastructure that support the investigation process, the investigator's knowledge of cybercrime crime, and legal awareness of the community that is still not optimal.Key Words: Investigation - Criminal acts of decency – Social Media